Financial Integration and Macroeconomic Volatility - Terrones, Marco (IMF Working Papers; Working Paper ;, 2003)
This paper examines the impact of international financial integration on macroeconomic volatility in a large group of industrial and developing economies over the period 1960-99. We report two major results: First, while the volatility of output growth has, on average, declined in the 1990s relative to the three preceding decades, we also document that, on average, the volatility of consumption growth relative to that of income growth has increased for more financially integrated developing economies in the 1990s. Second, increasing financial openness is associated with rising relative volatility of consumption, but only up to a certain threshold. The benefits of financial integration in terms of improved risk-sharing and consumption-smoothing possibilities appear to accrue only beyond this threshold.